AUTO UPKEEP : Maintenance, Light Repair, Auto Ownership, and How Cars Work - Gray, Michael E.; Gray, Linda E. (Rolling Hills Publishing, 2018)
From choosing an insurance policy to performing basic maintenance and repair, Auto Upkeep is the do-it-yourself automotive guide for the driver in you. Auto Upkeep keeps you safe and your vehicle reliable by providing easy-to-follow information with detailed pictures and drawings. Discover how to choose a quality repair facility, buy a car, handle roadside emergencies, diagnose common problems, and communicate effectively with technicians - all while saving money